(untitled) (American Journal of Islam and Society, 1985)
I. INTRODUCTION -THE MAJOR CRITICS OF ISLAMIC ECONOMICS: This paper attempts to respond to the critics who, on various grounds, oppose the development of Islamic economics. The author feels that a scientific response to these critics is the responsibility of the Islamic economists. It is believed that such a response would be educational for the critics and their followers. It would enable them not only to understand the scientific nature of Islamic economics but would also allow them to appreciate that the development of the Shari’ah paradigm ofislamic economics is, in fact, the beginningofascientific revolution in economics. Given the bases of their arguments, these critics of Islamic economics can be classified into the following three schools of thought. 1) The Adjusted Capitalism School: According to this school the fundamental principles of the Islamic economic system are the same as those of capitalism. In support of this assertion they point out that like capitalism, Islam also allows the right to private property, free enterprise, and market economy. They, however, acknowledge that certain adjustments need to be made in capitalism to bring it in conformity with Islamic principles. They hold that these adjustments should be made according to Islam’s distinction between Haram and Halal, and Islam’s teachings in financial and fiscal areas; namely, riba and zakat. According to this school, if these areas of capitalism are adjusted according to Islamic requirements, then the adjusted form of capitalism will be nothing but the Islamic economic system. Thus this school holds that the conventional economic theory, with only a few adjustments, is fully capable of generating the Islamic economic system. Hence, they see no scientific justification for the development of Islamic economics toward the creation and establishment of an Islamic economic system ...